Pengaruh Tax Avoidance, Leverage dan Persediaan terhadap Audit Report Lag dengan Ukuran Perusahaan sebagai Variabel Moderating - Hermanto; Nurriyah (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to examine the effect of Tax Avoidance, Leverage and Inventory on Audit Report Lag with Firm Size as a moderating variable. The information presented in this scientific paper consists of all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 in the form of 12 companies and reduced after testing several criteria to 10 companies and a total of 50 companies studied according to the research criteria. The results of this study are: tax avoidance does not affect audit report lag positively, leverage affects audit report lag positively, Inventory Turnover does not affect audit report lag negatively, tax avoidance does not moderate company size on audit report lag positively, leverage moderates firm size on audit report lag negatively, inventory turnover does not moderate firm size on audit report lag positively. The technique for determining the sample for this study was non-probability sampling, using purposive sampling.